Social Development of Children After Habituation Healthy Protocols During the Pandemic Covid 19 - Riwayati Zein; Tiara Fadillah Annisa Asfen; Hendrizal Hendrizal; Winda Noprina (Journal of Early Childhood Care and Education, 2022)
The presence of the corona virus forced the Aisyiyah 14 Ampang Padang Kindergarten students to become accustomed to health precautions during the pandemic, which served as the inspiration for this study. This study's goal was to explain how the adoption of health regulations during the pandemic affected the social development of kids in TK Aisyiyah 14 Ampang Padang who were between the ages of 5 and 6. This study combines quantitative data analysis methods with descriptive research. The 70 kids who made up the study's population were all members of group B at TK Aisyiyah 14 Ampang Padang. Observation logs, field notes, photographic and video recordings, and organized interviews are examples of research tools. The study's findings demonstrate how well-stimulated social behavior, social competence, and social responsibility are encouraged by the adoption of health protocols during the pandemic, ensuring that kids are aware of and obedient when wearing masks, washing their hands, and keeping their distance when interacting with other people.